2018
DOI: 10.1155/2018/6134787
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Marrow Contains Mesenchymal Stromal Stem Cells That Differentiate In Vitro into Contractile Myofibroblasts Controlling T Lymphocyte Proliferation

Abstract: Mesenchymal stromal stem cells (MSC) that reside in the bone marrow (BM) can be amplified in vitro. In 2-dimension (D) cultures, MSC exhibit a morphology similar to fibroblasts, are able to inhibit T lymphocyte and natural killer cell proliferation, and can be differentiated into adipocytes, chondrocytes, or osteoblasts if exposed to specific media. Here we show that medullar MSC cultured in 2D formed an adherent stroma of cells expressing well-organized microfilaments containing α-smooth muscle actin and nonm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 57 publications
3
40
1
1
Order By: Relevance
“…MSC extraction, amplification, seeding in 3D-solid collagen scaffolds and basic contraction characteristics have been previously described [27,28]. The present experiments were performed with the same type of MSC-laden collagen scaffolds used in a previous study [10]. Scaffolds consisted in clinical hemostatic sponges (Avitene™ ultrafoam collagen, ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSC extraction, amplification, seeding in 3D-solid collagen scaffolds and basic contraction characteristics have been previously described [27,28]. The present experiments were performed with the same type of MSC-laden collagen scaffolds used in a previous study [10]. Scaffolds consisted in clinical hemostatic sponges (Avitene™ ultrafoam collagen, ref.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous myofibroblasts are present in pathological tissues, such as cancer stroma, and in fibrotic processes [7][8][9]. Finally, considering bioengineered tissues, human medullar MSCs seeded into collagen scaffolds display contractile features, similar to those of the human placenta [10]. Myofibroblast contractility is empowered by the molecular motor NMMIIA [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The human femoral heads were collected during surgical interventions for hip replacements, according to the CCER, and after patients were informed and gave their written consent. MSC extraction, amplification and MSC seeding in 3D-solid collagen scaffolds have been previously described in detail [1]. Thus, BM-derived MSCs seeded in collagen scaffolds have been shown to form an adherent cell stroma with well-organized microfilaments expressing α-SMA and a high level of NMMIIA, but they are devoid of muscle myosin.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we reported that mesenchymal stem cells (MSCs) derived from human bone marrow (BM) and seeded in solid 3D-collagen scaffolds differentiated into myofibroblasts in the presence of human platelet lysate (HPL) and contracted when exposed to KCl or an electrical field [1]. Myofibroblasts in collagen scaffolds were shown to contain α-smooth muscle actin (α-SMA) and non-muscle myosin II (NMMIIA), which were colocalized, but no muscle myosin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation